2016
DOI: 10.1259/dmfr.20150296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of mandibular canal visibility on cross-sectional cone-beam CT images: a retrospective study

Abstract: The MC was visualized only in just over half of the CBCT images. Age, gender and location had significant effects on the visibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
(37 reference statements)
3
16
3
2
Order By: Relevance
“…CT seems to be a useful modality for visualizing the course of the MC, but there are limitations to the visibility of the MC. The proportion of visible MCs ranged from 42% to 92% in previous reports, 2,4,6,11,12 compared with 68% (100/147 MCs) in this study. Our relatively lower rate of detection might be due to a strict definition for visible, but we used it to confirm whether the NVB on MRI could really be matched to the MC on CT.…”
Section: Discussioncontrasting
confidence: 50%
“…CT seems to be a useful modality for visualizing the course of the MC, but there are limitations to the visibility of the MC. The proportion of visible MCs ranged from 42% to 92% in previous reports, 2,4,6,11,12 compared with 68% (100/147 MCs) in this study. Our relatively lower rate of detection might be due to a strict definition for visible, but we used it to confirm whether the NVB on MRI could really be matched to the MC on CT.…”
Section: Discussioncontrasting
confidence: 50%
“…In Types Ib and IIIb, it is easy to locate the mandibular canal on CBCT as there is an obvious space for the neurovascular bundles. This is probably why previous studies had a lower detection rate of the superior wall (Miles et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…Jacobs et al () detected the mandibular canal on paraxial views in 98% of cases with invisibility or poor visibility of its course in 20%. Miles et al () identified the mandibular canal in 56% of examined sites using CBCT and concluded that visibility differs between age, sex, and area examined.…”
Section: Introductionmentioning
confidence: 99%
“…Tracing the inferior alveolar nerve canal is an essential task for implant treatment planning but was not possible to do in the skull we used; the canal was visible only at some cross sections but could not be traced continuously. Miles, Parks, Eckert, and Blanchard () studied the visibility of mandibular canal in CBCT scans, and it was visible in only 56% of the studied subjects, with younger patients (47–56 years) and females showing lower visibility than older patients (65+ years) and males. When the visibility was further studied according to the location, at the premolar site, older males had higher visibility, whereas females had less visibility, compared with molar sites (Miles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Miles, Parks, Eckert, and Blanchard () studied the visibility of mandibular canal in CBCT scans, and it was visible in only 56% of the studied subjects, with younger patients (47–56 years) and females showing lower visibility than older patients (65+ years) and males. When the visibility was further studied according to the location, at the premolar site, older males had higher visibility, whereas females had less visibility, compared with molar sites (Miles et al, ). Presurgical assessment of the buccal plate thickness is needed to plan the surgical technique in cases of ridge preservation or immediate implant procedures.…”
Section: Discussionmentioning
confidence: 99%